The Lived Experiences of Self-Efficacy Among First-Year Santri in Islamic Boarding School - Fildzah Zakiroh Azatil 'Ismah; Fitrania Maghfiroh (Al-Qalb : Jurnal Psikologi Islam, 2026)
First-year students in Islamic boarding schools experience a demanding adaptation period, involving adjustment to a new environment, strict rules, structured routines, and a digital-free policy. These conditions often impact students' self-efficacy, which plays a crucial role in academic, social, and emotional adjustment. This study aims to explore first-year students' lived experiences in developing self-efficacy during the adaptation process in a digital-free Islamic boarding school environment. This study employed a qualitative method with a phenomenological approach. Five first-year students were selected through purposive sampling and interviewed in-depth using a semi-structured interview guide. Data were analyzed using Miles and Huberman's interactive model, including data collection, data reduction, data presentation, and conclusion drawing. Data validity was strengthened through member checking and researcher reflection to minimize bias. The findings revealed three main themes: (1) dynamics of adaptation and emotional regulation, highlighting how students cope with stress, homesickness, and strict routines through religious adjustment; (2) academic experiences and self-efficacy formation, demonstrating that mastery experiences, teacher feedback, and motivation rooted in religious values strengthen students' self-confidence; and (3) social support and identity development, describing the role of peers, mentors, and religious teachers in fostering a stable personal and religious identity that strengthens self-efficacy. This study concludes that the development of self-efficacy among first-year students attending Islamic boarding schools is shaped by the interaction of emotional, academic, social, and spiritual factors within a structured, digital-free environment. These findings provide insights for developing holistic mentoring strategies to support student adaptation and self-efficacy.